Injection procedures osteoarthritis and related conditions - Stitik, Todd P.; SpringerLink (Online service). (New York Springer, 2011)
Joint injection is a particularly beneficial treatment for inflammatory and degenerative conditions in the upper and lower extremities and the spine. The technique is effective for managing pain after other treatments have failed and, though the procedure has historically been performed by orthopedists, physiatrists, rheumatologists and interventional radiologists, the ease with which injection procedures can be integrated into a physician?s practice have led to increased interest from family and sports medicine doctors. Injection Procedures: Osteoarthritis and Related Conditions is focused on practical, step-by-step guidelines to performing image-guided injection procedures. It includes pearls and pitfalls, useful images from real procedures, and documentation templates for including information in a patient?s medical record. With chapters dedicated to the shoulder, elbow, wrist, hand, hip, knee, ankle and foot in addition to practical chapters on incorporating these procedures into a daily practice, this book is a comprehensive handbook for any physician interested in offering injection procedures as an option to his or her patients.
Basic principles of joint and soft tissue injection procedures -- Pharmacotherapy of joint and soft tissue injections -- Viscosupplementation -- Low back pain: considerations of when to refer patients for interventional spine procedures -- Administrative aspects of office-based injection procedures -- The shoulder -- The elbow -- The wrist -- The hand -- The hip -- The knee and its region -- The ankle and the foot.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Injections -- Handbooks, manuals, etc; Electronic books